Les contentieux du travail en droit anglais - Slynn, Sir Gordon (Les Cahiers de droit, 1982)
In this article, the author describes the British system of Labour Tribunals. These Tribunals, which are composed of jurists and non-jurists have jurisdiction to hear claims dealing with unlawful dismissal, discriminatory practices and other such matters. Although the workload is impressive, there is easy access to the Tribunals and a flexible procedure is used. An appeal on questions of law is provided for from those Tribunals to the Employment Appeal Tribunal, which is composed of one judge and two non-jurists. The author has acted as chairman of the Employment Appeal Tribunal and is clearly in favor of such a mixed composition. The article describes the decision-making process of the Appeal Tribunal and its powers.